Defining the optimal gradient doped #1#1#1=≤ ==≥ =PrFrReYb^3+:YAG disk for room and low temperature diode pumped solid-state laser operations. (1st September 2014) - Chanteloup, J.-C.; Arzakantsyan, M.; Marrazzo, S.
Abstract: We propose a general methodology to define the optimum doping ion volume distribution required for an efficient solid-state laser amplifier. This approach is illustrated in the context of two experimental diode pumped Yb:YAG amplifiers operating at 300 and 160 K. Processing of such tailored gain media is now possible through horizontal direct crystallization.